THE DEVELOPMENT OF LEARNING VIDEOS WITH THE PROBLEM-SOLVING APPROACH BY USING SCREENCAST O MATIC - Fury Styo Siskawati; Tri Novita Irawati; Sayyidati Zahro Salsabila (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2024)
Starting from students and teachers need interesting and innovative learning media that can help teachers during the learning process in class so develop the learning video as mathematical learning media. The purpose of the research is to describe the results of the developed learning video by using the problem-solving approach with screencast o matic application. The research is R&D research with the ADDIE model. The data collecting methods used are questionnaire, interview, observation, test, and documentation. Then for data analysis methods used are analysis of the item, product feasibility test analysis, and product practicality test analysis. The research result is material validation obtained a score of 3.19 while media validation obtained a score of 3.67 so can be concluded that the learning video is valid and has appropriate criteria for use. Then the result of the student’s response obtained an average score of 76% and the teacher’s response showed results of 80% which means that learning video is practical to use. The conclusion of this research is the developed learning video covers some steps of analysis, design, development, implementation, and evaluation then the result of this developed learning video is valid with an average value are 3,43 from material and media validators and practical to use with the average value are 78% from teacher and student response. The suggestion for this research is to make learning videos interesting for the user needs to improve the appearance and give reality problems in the case.Berawal dari siswa dan guru yang memerlukan media pembelajaran menarik dan inovatif yang dapat membantu guru selama proses pembelajaran di kelas maka dikembangkanlah video pembelajaran sebagai media pembelajaran matematika. Tujuan penelitian adalah untuk mendeskripsikan hasil pengembangan video pembelajaran dengan pendekatan pemecahan masalah berbantuan aplikasi screencast o matic. Penelitian ini merupakan penelitian R&D dengan model ADDIE. Metode pengumpulan data yang digunakan adalah angket, wawancara, observasi, tes, dan dokumentasi. Kemudian untuk metode analisis data yang digunakan adalah analisis uji kelayakan produk, dan analisis uji kepraktisan produk. Hasil penelitian validasi materi memperoleh skor 3,19 sedangkan validasi media memperoleh skor 3,67 sehingga dapat disimpulkan video pembelajaran tersebut valid dan memenuhi kriteria layak untuk digunakan. Kemudian hasil respon siswa memperoleh skor rata-rata 76% dan respon guru menunjukkan hasil 80% yang berarti video pembelajaran praktis untuk digunakan. Kesimpulan dari penelitian ini adalah video pembelajaran yang dikembangkan meliputi beberapa langkah yaitu analisis, desain, pengembangan, implementasi, dan Evaluasi, hasil video pembelajaran yang dikembangkan ini valid dengan rata-rata skor 3,43 dari validator materi dan media serta praktis untuk digunakan dengan rata-rata skor sebesar 78% dari respon siswa dan guru. Saran dari penelitian ini adalah membuat video pembelajaran yang lebih menarik bagi pengguna, perlu dilakukan perbaikan tampilan dan memberikan permasalahan yang nyata pada kasus.